2009
DOI: 10.2478/v10096-009-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

The emplacement mode of Upper Cretaceous plutons from the southwestern part of the Sredna Gora Zone (Bulgaria): structural and AMS study

Abstract: Several plutons located in the southwestern part of the Sredna Gora Zone -Bulgaria are examples of the Apuseni-Banat-Timok-Sredna Gora type of granites emplaced during Late Cretaceous (86-75 Ma) times. The studied intrusive bodies are spatially related to and deformed by the dextral Iskar-Yavoritsa shear zone. The deformation along the shear zone ceased at the time of emplacement of the undeformed Upper Cretaceous Gutsal pluton, which has intruded the Iskar-Yavoritsa mylonites. A clear transition from magmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…Although the origin of the Strandzha, Circum‐Rhodope, and the Rhodope Units is somewhat ambiguous, they certainly have been part of the European continental margin since at least Cretaceous times [ Okay et al , ; Schmid et al , ; Burg , ]. The Rhodope Unit is separated from the Dacia Mega‐Unit along the right‐lateral Maritsa fault system that comprises several NW‐SE trending shear zones, among others the Iskar‐Yavoritsa shear zone, which became active in the Late Cretaceous [ N. Georgiev et al , ; Naydenov et al , ].…”
Section: Regional Geologymentioning
confidence: 99%
“…Although the origin of the Strandzha, Circum‐Rhodope, and the Rhodope Units is somewhat ambiguous, they certainly have been part of the European continental margin since at least Cretaceous times [ Okay et al , ; Schmid et al , ; Burg , ]. The Rhodope Unit is separated from the Dacia Mega‐Unit along the right‐lateral Maritsa fault system that comprises several NW‐SE trending shear zones, among others the Iskar‐Yavoritsa shear zone, which became active in the Late Cretaceous [ N. Georgiev et al , ; Naydenov et al , ].…”
Section: Regional Geologymentioning
confidence: 99%
“…This process is associated with ∼500 km retreat of the Hellenic slab in Cenozoic times [ Jolivet and Brun , 2010]. The scenario of post‐Early Cretaceous nappe stacking in the Rhodope Mountains at a “proto‐Hellenic” active margin is supported by widely observed synmetamorphic top‐southwest shearing and by the existence of Late Cretaceous arc volcanism in the Sredna Gora Mountains north of the Rhodopes in central Bulgaria [ Boccaletti et al , 1978; von Quadt et al , 2005; Georgiev et al , 2009].…”
Section: Geological Settingmentioning
confidence: 99%
“…[e.g., Boccaletti et al, 1978;Georgiev et al, 2009], which is part of the extensive Apuseni-Banat-Timok-Srednogorie belt. Geochronological studies in the Sredna Gora revealed a general southward younging of the magmatism, from circa 92 Ma in the north to circa 78 Ma in the south [von Quadt et al, 2005].…”
Section: Evidence For Late Cretaceous-tertiary Northward Subductionmentioning
confidence: 99%